Species richness and composition assessment of spiders in a Mediterranean scrubland - Cardoso, Pedro (2007)
Abstract Intensive fieldwork has been undertaken in Portugal in order to develop a standardized and optimized sampling protocol for Mediterranean spiders. The present study had the objectives of testing the use of semi-quantitative sampling for obtaining an exhaustive species richness assessment of spiders and testing the effects of day, time of day, collector and sampling method on the collected species richness and composition of a Mediterranean scrubland. The collecting summed 224 samples corresponding to one person-hour of effective fieldwork each. In total, 115 species were captured, of which 110 were recorded inside a delimited one-hectare plot, corresponding to more than 70% of the about 160 estimated species. Although no estimator reached the asymptote, the Michaelis-Menten curve behaviour indicates that the estimated richness should be accurate. Most different sampling approaches (day, time of day, collector and sampling method) were found to influence richness, abundance or composition of the samples to some extent, although sampling method had the strongest influence whereas “collector” showed no effect at all. The results support the idea that the only variables that need to be controlled in similar protocols are the sampling methods and the time of day when each method is executed. We conclude that populations in structurally simple habitats present narrower peaks of adult abundance, which implies higher percentages of juveniles in samples. Finally, results also indicate that habitats with a relatively simple structure like scrublands may require as much sampling effort, in order to reach similar proportions of captured species in relation to the estimated richness, as habitats that are much more complex.